2019
DOI: 10.3389/fimmu.2019.00213
|View full text |Cite
|
Sign up to set email alerts
|

Increased Regulatory T-Cell Activity and Enhanced T-Cell Homeostatic Signaling in Slow Progressing HIV-infected Children

Abstract: Pediatric slow progressors (PSP) are rare ART-naïve, HIV-infected children who maintain high CD4 T-cell counts and low immune activation despite persistently high viral loads. Using a well-defined cohort of PSP, we investigated the role of regulatory T-cells (T REG ) and of IL-7 homeostatic signaling in maintaining normal-for-age CD4 counts in these individuals. Compared to children with progressive disease, PSP had greater absolute numbers of T REG , skewed toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 92 publications
(101 reference statements)
0
15
1
4
Order By: Relevance
“…To be noted however, Treg expansion seems insufficient to suppress systemic immune activation in VNPs, as previously reported in studies of untreated chronic HIV infection associated with high viral replication [reviewed in Chevalier and Weiss (55)]. In contrast to our study, Roider et al (56) has delineated a possible role for Treg-mediated suppression of immune activation in a pediatric cohort resembling VNPs. The discordance in the relationship between Tregs and immune activation observed in VNPs and pediatric slow progressors may reflect the disparate immune responses to viral infection observed in a developing vis-à-vis mature immune system (57).…”
Section: Discussioncontrasting
confidence: 49%
“…To be noted however, Treg expansion seems insufficient to suppress systemic immune activation in VNPs, as previously reported in studies of untreated chronic HIV infection associated with high viral replication [reviewed in Chevalier and Weiss (55)]. In contrast to our study, Roider et al (56) has delineated a possible role for Treg-mediated suppression of immune activation in a pediatric cohort resembling VNPs. The discordance in the relationship between Tregs and immune activation observed in VNPs and pediatric slow progressors may reflect the disparate immune responses to viral infection observed in a developing vis-à-vis mature immune system (57).…”
Section: Discussioncontrasting
confidence: 49%
“…Tregs inhibit the activation of both innate and adaptive immune response via inhibitory surface molecules (like CTLA-4 and LAG-3) and by the secretion of immunosuppressive cytokines (i.e., IL-10, TGF-β, and IL-35) ( 38 , 39 ). It has been recently reported that slow-progressors HIV-infected children secreted higher levels of IL-10 compared to those who progressed and had higher proliferation of Tregs ( 40 ). Similarly, it is possible that Tregs and Bregs in SARS-CoV-2-infected children constrains inflammation/immune activation, likely through the release of IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on integration sites of proviral genomes have shown that long-term virologic suppression is associated with changes in the composition of the viral reservoir, favoring sites associated with maintenance of deep viral latency (8,43,44). The immune-selective pressure driving the establishment of the latent reservoir may be differentially affected by the underdeveloped immune system of infancy (45). Other factors that can account for the differences in reactivation are the immune landscape in which HIV infection is established, including hyporesponsiveness due to higher proportions of T regulatory cells in early infancy and childhood (46)(47)(48); as well as differences in the distribution of the latent HIV reservoir in different memory T cell subsets (49,50).…”
Section: Discussionmentioning
confidence: 99%